Entrepreneurial Orientation on Small and Medium Performance: The Role of Religiosity as moderator - Maidia Putri; Perengki Susanto (Marketing Management Studies, 2021)
This study was to analyze the effect of entrepreneurial orientation on the performance of small and medium enterprises (SMEs), as well as how religiosity moderate these relationships. The population was all managers or owners of SMES in the commodity of superior business products/services in Pesisir Selatan Regency. The sampling technique used a non-probability approach, namely the purposive sampling. In the data analysis, 240 samples were used as a sample size. The Smart-PLS software is used in this study to perform variance-based structural equation modeling (VB-SEM). The findings show that (i) entrepreneurial orientation has a positive and significant effect on SME performance, (ii) In these relationships, the role of religiosity as a moderator is not supported. The managerial implications will be discussed later.